Evaluation of polymeric PLGA nanoparticles conjugated to curcumin for use in aPDT - Renata Celi Carvalho de Souza Pietra; Rosana Carvalho Cruz; Carla Nunes Melo; Lívia Bomfim Rodrigues; Patrícia Campi Santos; Gabriel Pissolati Matos Bretz; Betânia Maria Soares; Gerdal Roberto de Sousa; Marcus Vinícius Lucas Ferreira; Patrícia Silva Cisalpino; Paula Prazeres Magalhães; Luiz de Macêdo Farias; et al. (Universidade de São Paulo, 2017)
ABSTRACT Antimicrobial photodynamic therapy (aPDT) involves the association of a photosensitizing agent with a light source with the goal of causing apoptosis or microbial lysing. The use of compounds with natural active principles is gaining prominence throughout the world. Several studies from groups that are linked to the development of innovations in the pharmaceutical market have used natural dyes, such as curcumin, the efficacy of which has been demonstrated in aPDT trials. Difficulties related to physicochemical stability, solubility and cell penetration are some of the challenges associated with this field. The present work aimed to prepare, investigate the characteristics and improve the photodynamic activity of PLGA-based nanoparticles loaded with curcumin for use in aPDT therapy. Using the simple technique of emulsion during the evaporation of a solvent, the particles were built, characterized and tested against microorganisms with importance for medicine and dentistry. The results revealed that the particles were able to protect the curcumin against degradation and eliminate some microorganism species at nanomolar concentrations.